In Vitro Biological Activities of Fruits and Leaves of Elaeagnus multiflora Thunb. and Their Isoprenoids and Polyphenolics Profile - Sabina Lachowicz; Ireneusz Kapusta; Michał Świeca; Carla M. Stinco; Antonio J. Meléndez-Martínez; Anna Bieniek (MDPI AG, 2020)
The objective of this study was in-depth identification of carotenoids and polyphenolic compounds in leaves and fruits of Elaeagnus multiflora Thunb. An additional aim was to assay their antioxidant and in vitro biological activities (the ability to inhibit pancreatic lipase, α-amylase, and α-glucosidase activity) of two cultivars: 'Sweet Scarlet' and 'Jahidka'. Study results showed the presence of 70 bioactive compounds, including 20 isoprenoids and 50 polyphenols. The profile of identified bioactive compounds had not been examined in this respect until now. The total carotenoid, chlorophyll, and polyphenol levels and antioxidant activity of the foliar samples were virtually identical in both cultivars and clearly higher relative to those in the fruits. On the other hand, the ability to inhibit pancreatic lipase, α-amylase, and α-glucosidase activity of the fruits was clearly higher as compared to the leaves. The highest amount of phenolic acids, flavonols, and polymeric procyanidins was in the 'Sweet Scarlet' for fruit and leaves, while the highest amount of chlorophylls and carotenoids was in the 'Jahidka'. The inhibition of α-amylase, α-glucosidase, and pancreatic lipase activities appeared to be better correlated with the carotenoid content, which warrants further studies of the possible anti-diabetic and anti-obesity actions of the major carotenoids found in the fruits (lycopene, phytoene, and lutein). In addition, strong correlation between antioxidant activity and phenols of E. multiflora Thunb. components can be effective in removing reactive oxygen species. The results of our study show that both the fruits and leaves of E. multiflora Thunb. can be important for health promotion through the diet and for innovating in the industry of functional food and (nutri)cosmetics.